Poland's Role in Ukraine's Security Amid the Challenge of Migration - Pankowski, Rafal; Czerska-Shaw, Karolina; Rangelov, Iavor (My University, 2023)
PeaceRep’s Ukraine team convened a seminar on 10 March 2023 to discuss Poland’s response to the war against Ukraine. The seminar drew together members of PeaceRep’s regional network in Ukraine’s neighbouring countries, along with our academic staff at the LSE. The discussion identified some of the ways in which civic mobilisations by Ukrainian activists in Poland’s are shaping Ukraine’s domestic security needs, and the downstream risks that may lie ahead. This readout contains a non-verbatim summary of key points made by panellists in their presentations. This readout is published as part of the programme of work undertaken by PeaceRep’s Ukraine team to assess the medium-term security challenges facing the region in light of the full-scale Russian invasion.
Keywords: Peace Processes; Poland; Ukraine